Historical Trauma, Race-based Trauma and Resilience of Indigenous Peoples: A Literature Review - Fast, Elizabeth; Collin-Vézina, Delphine (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2010)
This literature review examines the various responses to trauma suffered by Indigenous peoples as a result of governmental policies geared towards assimilation. Both traumatic and resilient responses are demonstrated at the individual, family and community levels. Much of the research that has been done in the United States to develop theories around historical trauma and race-based traumatic stress may also be applied to Canada’s First Nations due to similar histories of oppression and colonization. Overall, the research finds that self government and a connection to culture and spirituality result in better outcomes for Indigenous peoples.